Pilot Study: Different Leg Muscle Activation When Walking on Stable, Unstable & Slippery Floors : (Parameters Using Surface Electromyograph) - Arif Pristianto; Nadeputri, Anindya Evan Salma Majiid; Susilo, Taufik Eko; Santoso, Totok Budi (Universitas Muhammadiyah Surakarta, 2024)
Introduction: Muscle activation is the interaction of intracellular cell fluid and extracellular cell fluid that occurs in the cell membrane channel and can also be defined as the movement of muscle contraction and relaxation accompanied by changes in muscle fibre length. To determine differences in muscle activation in the legs (m. gastrocnemius, m. tibialis anterior, m. rectus femoris, m. biceps femoris longum, m. gluteus maximus) when walking in various floor/base conditions (stable, unstable, and slippery) using a Surface Electromyograph (sEMG). Methods: The research method used is Experimental Single Group Design where the researcher involves only 1 group consisting of 5 subjects. Results: The results of this study first used the repeat ANOVA test with scores obtained on stable floor conditions (0.000), unstable floor conditions (0.000), and slippery floor conditions (0.000). Conclusion: From the results of research that has been carried out, it can be concluded that there are differences in leg muscle activation as measured using Surface Electromyograph (sEMG) when walking on a stable, unstable, and slippery floor.